The Isolation and Identification of Bacteria with Potential for Mercury (Hg) Bioremediation from the Kahayan River - Chuchita Chu; Zimon Pereiz; Zahrotun Nafisah; Efriyana Oksal; Miranti Maya Sylvani; Ahmad Irawan; Febrianto Alfi (Jurnal Kimia Fullerene, 2026)
The Kahayan River in Central Kalimantan is one of the waterways utilized for traditional gold mining that employs amalgamation techniques. The application of this method poses a significant risk of environmental pollution and degradation. This study was conducted to evaluate the capacity of bacteria to act as bioremediation agents for mercury (Hg) at different concentrations. The methodology involved inoculating sediment samples into Zobell 2216E medium, isolating and purifying bacterial colonies on Nutrient Agar (NA), followed by bacterial identification and assessment of mercury degradation using an Atomic Absorption Spectrophotometer (AAS). The findings revealed that isolate 34 was able to remove 132.73 ppm of Hg from an initial concentration of 250 ppm (equivalent to a 53.09% reduction), whereas isolate 108 removed 139.68 ppm, corresponding to a 55.87% reduction.